2002
DOI: 10.1051/0004-6361:20020107
|View full text |Cite
|
Sign up to set email alerts
|

Classical novae in outburst: The early evolution of the ultraviolet continuum

Abstract: Abstract. In the framework of a phenomenological study of the ultraviolet properties of classical novae in outburst, we have selected 12 objects among the best monitored at low resolution with the IUE satellite, and studied the temporal evolution of the ultraviolet continuum and of the O i 1300Å line flux during the early post-outburst phase. We confirm that the UV flux maximum takes place systematically after the visual maximum and that its time delay is a linear function of t3. A linear dependence on t3 is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(88 citation statements)
references
References 36 publications
(28 reference statements)
3
85
0
Order By: Relevance
“…The progressive hardening of the UV spectrum stops after day 10, when the C(1455-2885) color index stabilizes around a value of zero. Both these features are a common property of the novae studied by Cassatella et al (2002). Figure 3 reports, as a function of time, the observed flux in the most prominent UV emission lines, as measured by us from the available IUE low-resolution spectra.…”
Section: Evolution Of the Uv Continuummentioning
confidence: 73%
See 3 more Smart Citations
“…The progressive hardening of the UV spectrum stops after day 10, when the C(1455-2885) color index stabilizes around a value of zero. Both these features are a common property of the novae studied by Cassatella et al (2002). Figure 3 reports, as a function of time, the observed flux in the most prominent UV emission lines, as measured by us from the available IUE low-resolution spectra.…”
Section: Evolution Of the Uv Continuummentioning
confidence: 73%
“…This approximation is reasonably accurate in a very narrow wavelength range around UV 1455 Å flux (Cassatella et al 2002; Paper III) near its peak. IR and optical fluxes are calculated from free-free emission by using physical values of our wind solutions.…”
Section: Optically Thick Wind Modelmentioning
confidence: 85%
See 2 more Smart Citations
“…Their time-normalized light curves are almost independent of the WD mass, chemical composition of ejecta, and wavelength. also found that their UV 1455 Å model light curves (Cassatella et al 2002), interpreted as photospheric blackbody emission, are also time-normalized by the same factor as in the optical and NIR light curves. Using the fact that the time-scaling factor is closely related to the WD mass, the authors determined the WD mass and other parameters for a number of well-observed novae (e.g., , 2010Hachisu et al 2008;).…”
Section: Introductionmentioning
confidence: 84%